Progression of Cognitive, Functional and Neuropsychiatric Symptom Domains in a Population Cohort with Alzheimer’s Dementia The Cache County Dementia Progression Study - Tschanz, JoAnn T. (2011)
OBJECTIVES: Progression of Alzheimer’s dementia (AD) is highly variable. Most estimates derive from convenience samples from dementia clinics or research centers where there is substantial potential for survival bias and other distortions. In a population-based sample of incident AD cases, we examined progression of impairment in cognition, function, and neuropsychiatric symptoms, and the influence of selected variables on these domains. DESIGN: Longitudinal, prospective cohort study SETTING: Cache County (Utah) PARTICIPANTS: 328 persons diagnosed with Possible/Probable AD MEASUREMENTS: Mini-Mental State Exam (MMSE), Clinical Dementia Rating sum-of-boxes (CDR-sb), and Neuropsychiatric Inventory (NPI). RESULTS: Over a mean follow-up of 3.80 (range 0.07–12.90) years, the mean (S.D.) annual rates of change were −1.53 (2.69) on the MMSE, 1.44 (1.82) on the CDR-sb, and 2.55 (5.37) scale points on the NPI. Among surviving participants, 30–58% progressed less than one point/year on these measures, even 5–7 years after dementia onset. Rates of change were correlated between MMSE and CDR-sb (r=−0.62, df=201, p<0.001) and between the CDR-sb and NPI (r=0.20, df=206, p<0.004). Females (LR χ(2)=8.7, df=2, p=0.013) and those with younger onset (LR χ(2)=5.7, df=2, p=0.058) declined faster on the MMSE. Although one or more APOE ε4 alleles and ever-use of FDA-approved anti-dementia medications were associated with initial MMSE scores, neither was related to the rate of progression in any domain. CONCLUSIONS: A significant proportion of persons with AD progresses slowly. The results underscore differences between population- vs. clinic-based samples and suggest ongoing need to identify factors that may slow the progression of AD.